A novel multiple working modes parallel mechanism with variable workspace. (January 2020) - Li, Dian; Guo, Sheng; Qu, Haibo
In this paper, a novel three-degrees-of-freedom multiple working modes parallel mechanism with variable workspace is proposed. Several studies including kinematic and prescribed trajectory planning are performed. First, the degrees of freedom of mechanism's two working modes are calculated based on screw theory. A prototype made by 3D printer also has been developed. Then, the inverse/forward kinematics and Jacobian matrices are obtained. The workspace and singularity are also analyzed, which show that the proposed parallel mechanism possesses singularity-free internal workspace. Finally, a working mode determination method is presented, which can be used to obtain suitable workspace in order to fully contain a prescribed trajectory. An example trajectory is used to verify the reasonability of the proposed method.